THE RABBIT-FISHES (SIGANIDAE) OF TOMINI BAY, GORONTALO [Ikan-lkan Beronang (Siganidae) di Teluk Tomini, Gorontalo] - Andi Iqbal Burhanuddin (Jurnal Iktiologi Indonesia, 2005)
A study has been carried out to describe the rabbit-fishes of the family Siganidae at Tomini Bay, province of Gorontalo. The study was conducted from 8 to 16 August 2005. Ten species were identified: Sigiwus canaliculntus, S. doliatus, S. fuscescens, S. guttatus, S. javiis. S. lineatus, S. punctntus, S. spinus, S. vermiculntus and S', vulpinus. Description and local name available of each species was given.